Energy Efficiency Investigation of Fabric Filter and Electrostatic‐Fabric Integrated Precipitator in Coal‐Fired Power Plants in China - Hanxiao Liu; Liyuan Yu; Liming Wu; Lin Zhao; Ying Guo; Jun Liang; Ying Cui; Xiaowei Liu; Junxiao Chen; Meiling Liu (Energy Science & Engineering)
ABSTRACT Fabric Filter (FF) and Electrostatic‐Fabric Integrated Precipitator (EF) are the main equipment for industrial flue dust control, but their energy consumption levels are not yet clear especially after ultra‐low emission. In this paper, energy efficiency data of 22 sets of FF and 21 sets of EF before ultra‐low emission, and 9 sets of FF and 62 sets of EF after ultra‐low emission are systematically studied and analyzed by field testing and technical investigation. The results showed that after ultra‐low emission, the energy consumption and converted CO2 emission of FF and EF in coal‐fired power plants increased significantly. For FF (EF), the specific power consumption, power consumption per unit installed capacity and energy consumption corresponding to unit mass PM removal increased by 19.22% (12.60%), 127.49% (24.52%) and 25.45% (35.99%) respectively, and the converted CO2 emission corresponded increased by 0.45 × 10−4 (0.38 × 10−4) kg CO2/m³, 2.21 (0.42) kg CO2/MW·h and 3.01 (4.77) kg CO2/t PM on average. Compared with Electrostatic Precipitator (ESP), the power consumption, specific power consumption and converted CO2 consumption of FF and EF were generally lower, with a general rule shown as ESP > EF > FF. Under the premise of PM ultra‐low emission, the specific power consumption of different dust removal technologies and combinations was sorted as: ESP capacity expansion > ESP + WESP > LL‐ESP > EF + WESP > FF + WESP > Ultra‐clean EF > Ultra‐clean FF. Meanwhile, the results showed that the current Chinese standard GB 37484‐2019 was no longer applicable to evaluate the energy efficiency of the precipitator in ultra‐low emission units. This study can provide data support for evaluating the collaborative efficiency in pollution reduction and carbon reduction of ultra‐low emission units in FF and EF, as well as the national standard revision.